2021
DOI: 10.1002/cam4.4295
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world benefit of combination palbociclib and endocrine therapy for metastatic breast cancer and correlation with neutropenia

Abstract: Institutional review board obtained prior to the start of this study (ID: MCC 19591).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Different from our study, neutrophil levels were recorded at weeks 2, 4, 6, 8, 12, 16, 18, and 24. Lower neutrophil levels were found to be correlated with a lower risk of progression (13). On the contrary, according to the results obtained in our study, the development of neutropenia on days 10 and 28 did not affect the risk of progression in the palbociclib group.…”
Section: Discussionsupporting
confidence: 51%
“…Different from our study, neutrophil levels were recorded at weeks 2, 4, 6, 8, 12, 16, 18, and 24. Lower neutrophil levels were found to be correlated with a lower risk of progression (13). On the contrary, according to the results obtained in our study, the development of neutropenia on days 10 and 28 did not affect the risk of progression in the palbociclib group.…”
Section: Discussionsupporting
confidence: 51%
“…The interpretation of real-world studies may be limited by the lack of a comparator group, small sample size, short follow-up, and/or differences in outcome endpoint definitions 15 18 . Only a few comparative effectiveness analyses of CDK4/6 inhibitor outcomes in MBC have been published to date, including DeMichele et al (2021) and Brufsky et al (2021) using the Flatiron Health Analytic Database (Flatiron Health, New York, NY) and Ha et al (2022) from one academic institution (Breast Medical Oncology database; MD Anderson Cancer Center, Houston, TX) 19 – 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils have been shown to promote tumor growth and play a pro-angiogenic role by releasing matrix metalloproteinases that promote angiogenesis and play an immunosuppressive role by inhibiting CD8 + T cells. 11 Sun et al 12 studied the relationship between baseline ANC, NLR, and PFS in 165 patients with HR + / HER2- ABC treated with Palbociclib plus ET as first-line therapy. Univariate analysis revealed that ANC was significantly correlated with PFS, implying that the decrease in ANC suggested prolonged PFS.…”
Section: Hematologic-related Prognostic Parametersmentioning
confidence: 99%